Results of Complex Treatment of Chronic Disseminated Periodontitis in Patients Who Have Undergone Covid-19 (Eurasian Medical Research Periodical, 2023)
In recent times, the primary cause of patients seeking a dentist is paradont disease, leading to premature teeth clots, decreased quality of life due to bad breath, bleeding gums, and dental hyperesthesia. Based on the study, the results of the treatment of 112 patients examined from 2019 to 2022 were included in the orthopedic dentistry department of the Samarkand Regional Dental Department. According to the results of our study, chronic diffuse periodontitis was observed more in the group of patients aged 30-39 years – 39 (34.8%) patients. In chronic diffuse periodontitis, a clear clinical effect was obtained when the Prozone device was applied with a special disposable Period tip in the equivalent of 18 seconds, when the periodontal pockets were applied in combination with an ozonized solution of hypochlorite sodium. Index performance was two times lower. Cytobacterioscopic data prove that inflammation has decreased and eliminated throughout the year